The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.13005/ojc/330621
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Performance of Stainless Steel and Nickel Alloys in Aqueous Sodium Hydroxide as Revealed from Cyclic Voltammetry and Potentiodynamic Anodic Polarization

Abstract: The electrochemical behavior of nickel, Inconel 600, Incoloy 800 and 316 stainless steel electrodes in different concentration of NaOH solution was investigated using the cyclic voltammetry technique (CV). All the curves in the anodic branch of the CV are characterized by anodic dissolution peak (A), passive region (B), anodic dissolution peak (C) before oxygen evolution. In the case of the cathodic branch of CV there is one reduction peak (D) in case of Ni electrode but there are two reduction peaks (D and E)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The analyzed area showed an inclusion of about 29.7 µm 2 . This was also confirmed by the studies done by Abdallah et al [6][7][8] that showed the extent of pitting corrosion of the Inconel 600™ alloy when exposed to various acids and bases and that the grain boundary precipitates would correspond to (Cr -Fe) 23 C 6 and TiN.…”
Section: Results Using Potentiodynamic Polarization Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…The analyzed area showed an inclusion of about 29.7 µm 2 . This was also confirmed by the studies done by Abdallah et al [6][7][8] that showed the extent of pitting corrosion of the Inconel 600™ alloy when exposed to various acids and bases and that the grain boundary precipitates would correspond to (Cr -Fe) 23 C 6 and TiN.…”
Section: Results Using Potentiodynamic Polarization Analysissupporting
confidence: 80%
“…5 The corrosion rates reported varied between 0.033 and 0.8344 mm yr -1 and were obtained in solutions that varied between 0.01 M to 10.00 M, respectively. Extensive studies in using Inconel 600™ in nitric acid and caustic soda applications were performed by Abdallah et al [6][7][8] They made use of cyclic voltammetry to investigate the formation of the passivation film and compared it to other alloys such as Incoloy 800 and 316 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reactions occurring in the electrolyzer have slightly darkened the electrolyte. The use of (316 SS) electrodes would probably have prevented this (Abdallah et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Most inhibitors are organic compounds containing heteroatoms (N, O, S), unsaturated bonds and plane conjugated systems [2][3][4][5][6][7][8][9]. They are adsorbed on the steel surface and block it, thus preventing corrosion [9].…”
Section: Introductionmentioning
confidence: 99%